2015
DOI: 10.1124/mol.115.097758
|View full text |Cite
|
Sign up to set email alerts
|

Neuritogenic Activity of Tetradecyl 2,3-Dihydroxybenzoate Is Mediated through the Insulin-Like Growth Factor 1 Receptor/Phosphatidylinositol 3 Kinase/Mitogen-Activated Protein Kinase Signaling Pathway

Abstract: Tetradecyl 2,3-dihydroxybenzoate (ABG-001) is a lead compound derived from neuritogenic gentisides. In the present study, we investigated the mechanism by which ABG-001 induces neurite outgrowth in a rat adrenal pheochromocytoma cell line (PC12). Inhibitors of insulin-like growth factor 1 (IGF-1) receptor, phosphatidylinositol 3-kinase (PI3K), and extracellular signal-regulated kinase (ERK) 1/2 significantly decreased ABG-001-induced neurite outgrowth. Western blot analysis revealed that ABG-001 significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The compound contains a long alkyl chain of 14 carbons, two close hydroxyl groups on the benzene ring, and an ester linkage between the ring and alkyl chain ( Luo et al, 2011 ). ABG-001 can induce neurite outgrowth of PC12 cells like NGF via the IGF-1/PI3K/ERK signaling pathway ( Tang et al, 2015 ). In the present study, we tested the anti-diabetic effects of ABG-001 on STZ-induced diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The compound contains a long alkyl chain of 14 carbons, two close hydroxyl groups on the benzene ring, and an ester linkage between the ring and alkyl chain ( Luo et al, 2011 ). ABG-001 can induce neurite outgrowth of PC12 cells like NGF via the IGF-1/PI3K/ERK signaling pathway ( Tang et al, 2015 ). In the present study, we tested the anti-diabetic effects of ABG-001 on STZ-induced diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction and cDNA synthesis of white adipose tissue, liver, gastrocnemius muscle, pancreas, and hypothalamus were performed using the methods from previous studies ( Tang et al, 2015 ). The transcript levels were quantified by using CFX96-Touch (Bio-Rad, Hercules, CA, United States) and SYBR Premix EX Taq TM (Takara, Otsu, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NGF directly bound to the transmembrane-specific tyrosine receptor kinase A, and resulted in phosphorylation of ERKl/2. However, we found that activation of insulin-like growth factor 1 receptor (IGF-1R) is involved in ABG-001, an analogue of 15d induced neurite outgrowth of PC12 cells in recent study, 20) as the chemical structure of 15d is quite similar to that of ABG-001. Therefore, we presumed that the mechanism of 15d on neurite outgrowth is similar to ABG-001.…”
Section: 2)mentioning
confidence: 98%